2005
DOI: 10.1089/fpd.2005.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Variable Abattoir Conditions Affect Salmonella enterica Prevalence and Meat Quality in Swine and Pork

Abstract: Research suggests that abattoir holding pens pose significant Salmonella enterica risk to swine immediately preharvest. The goal of this study was to evaluate those factors related to holding that increased the prevalence of S. enterica in swine at slaughter. To accomplish this goal, we focused on holding time and flooring. Our objectives were to (1) compare Salmonella enterica prevalence among pigs held for short (15-45 min) versus long (up to 4 h) periods before slaughter; and (2) determine the impact of flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
(10 reference statements)
0
14
0
Order By: Relevance
“…Holding pigs in lairage for extended periods increases the contamination rate with Salmonella spp. because of the high prevalence of this pathogen in the lairage environment (Hurd et al, 2005;Larsen, Hurd, McKean, Griffith, & Wesley, 2004). Therefore, in the current study, a greater percentage of positive lymph node and caecal samples were expected to be linked to the lairage which suggests that other factors such as the farm may have had a role to play.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Holding pigs in lairage for extended periods increases the contamination rate with Salmonella spp. because of the high prevalence of this pathogen in the lairage environment (Hurd et al, 2005;Larsen, Hurd, McKean, Griffith, & Wesley, 2004). Therefore, in the current study, a greater percentage of positive lymph node and caecal samples were expected to be linked to the lairage which suggests that other factors such as the farm may have had a role to play.…”
Section: Discussionmentioning
confidence: 73%
“…within some abattoir environments and in the current study PFGE analysis showed the same Salmonella serotypes were isolated from the lairage environment within abattoirs on different sampling days. Previous authors have shown lairage pens to be highly contaminated before pigs entered (Hurd, Gailey, McKean, & Griffith, 2005;Rostagno et al, 2003;. Furthermore, Hurd et al (2005) demonstrated differences between solid concrete and slatted floors with 95% of solid and 68% of slatted testing positive for Salmonella spp.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The standing position and the scarce exploratory behaviour seemed to have prevented the contamination of pigs' body or mouth with the faeces present on the vehicle floor. Furthermore, despite this behaviour, the short exposure of pigs to manure might have limited their contamination anyway as it is known that the risk for carcass faecal contamination increases with the animals' exposure time to manure in the surrounding environment (Hurd et al 2005). For personal use only.…”
Section: Carcass Microbial Contaminationmentioning
confidence: 99%
“…The environmental factors contributing to the contamination of the mouth are not fully understood. However, it is expected that mouth contamination can result, at least in part, from the pigs' contact with manure present on the pen floor or walls while performing their natural exploratory behaviour (Hurd et al 2005). The presence of manure on the truck or lairage pen floor is a likely source of faecal bacteria (e.g., E. coli, Salmonella) and shedding rate of animals is known to be influenced by feed withdrawal time and stress (Gregory 1998;Reid et al 2002).…”
mentioning
confidence: 99%